Efeitos da gastrectomia vertical sobre o trato gastrointestinal em ratos obesos pela dieta de cafeteria - Capelassi, Angélica Novi (2016)
Obesity is a risk factor in the development of many diseases such as diabetes and hypertension. In addition, it is associated with the development of diseases in the gastrointestinal tract (GIT) such as gastroesophageal reflux and gastritis. Bariatric surgery has proved to be the only effective long-term treatment modality sustained effects for the treatment of morbid obesity and its comorbidities. Studies have shown that bariatric procedures affect the morphology and function of the GIT. Few studies have investigated the effects of sleeve gastrectomy (SG), a restrictive technique that reduces the size of the stomach on the GIT. Thus, our objective was to analyze the effect of SG on gastric histopathology and the morphology of the small intestine (duodenum, jejunum and ileum) in obese rats fed a cafeteria diet. For this study, 8-week-old Wistar rats were divided into two groups: control (CTL), which received standard diet, and cafeteria (CAF), which received cafeteria diet to induce obesity. After two months, the CAF group underwent pseudo-surgery (CAF PS) or sleeve gastrectomy (CAF SG). At three months after surgery obesity was verified and stomach, duodenum, jejunum and ileum were collected and analyzed. Body weight and retroperitoneal and perigonadal fat pads were higher in CAF PS animals compared to the CTL. The SG did not influence these parameters. Regarding the morphology of the stomach, we observed that the CTL animals showed normal morphology of this organ, while the CAF PS animals showed changes in the gastric mucosa with the presence of hyperemia, mild inflammatory infiltrate and diffuse in the mucosa and submucosa, as well as mild erosion of the gastric mucosa and atrophy. The SG exacerbated changes in the stomach. CAF SG animals showed severe erosion of the gastric mucosa, edema, moderate and diffuse inflammatory infiltrate in the mucosa and submucosa, as well as atrophy of the muscular layer and the body of the mucosa. In relation to morphometry of the small intestine, no changes were found in the duodenum, jejunum and ileum of CAF PS and CTL animals. However, CAF SG animals showed increase in total thickness of the duodenum, as well as increase in the thickness of the mucosa and submucosa layer and villi. The jejunum and ileum showed no change. In the summary cafeteria diet causes changes in the gastric mucosa without changing the small intestine. The SG, three months after the procedure, exacerbates gastric alterations and promotes changes in the duodenum morphometry.